Optimization of transporter slice profile on the second supply value - Tatyana P. Savostina; Bakir Imad Saed (Advanced Engineering Research, 2017)
Introduction. The paper discusses the problem of an uneven flow of the grain mass to the threshing which leads to the increased grain loss under the grain-harvesting process. The study purpose is to identify patterns of the effect of changing the second flow threshing both on the length of the drum, and on its width. This is resulting in the possibility of obtaining graphs of the optimal slice profile of the conveying device which ensures an even flow of the grain mass at the initial stages of threshing. Materials and Methods. Our research is aimed at obtaining high qualitative indicators of the threshing process by the separating device. Studies on the equal-dimensional distribution of the grain mass under the threshing process by the tangential-axial separating device in the zones depending on the change in the second feed value are provided. Obtaining qualitative indicators of the thrashing was achieved through the slice profile optimization. The experimental data whose processing gave the opportunity to determine the optimal slice profile were used. Research Results. The experimental results have provided background for graph plotting of the transporter cut profile on a variety of quantities of the used feed (4-12 kg/s). The resulting equations of these lines are obtained. The averaged slice profile for the entire group of curves on the grain mass feed value is developed. Discussion and Conclusions. The studies of the transporter slice profiles on the second feed value have led to the derivation of the cut curve equation for the uniform grain mass flow to the threshing. The validity approximation coefficient has shown high levels of the approximation accuracy.